China-U.S. Currency Conflict:The Economic and Legal Implications - Hani Albasoos (International Journal of Research In Business and Social Science, 2016)
Abstract: For more than a decade, China has a policy of managing its currency exchange rate (RMB) to limit its appreciation against other currencies like U.S dollar. This policy has been subjected to many criticisms from United States’ lawmakers as currency manipulation. The U.S. argues that China is gaining an advantage of export and attracting direct foreign investment at the expense of other countries including the United State. The claim also has included that China’s manipulation causes U.S. trade deficit as well as high rate of unemployment. Meanwhile, China’s policy makers argue that its policy of exchange rate is a mechanism tool to enhance the development of the country and attaining market growth to make China rich and powerful. This research paper underlines the root of this argument and how china’s currency policy has affected both economics of U.S. and China. Many economists have emphasized on the appreciation of RMB as an important factor to attain the trade balance. However, this research argues that the appreciation is not going to matter. Pressure has been put on Obama’s Administration to push China to appreciate its currency and to designate China as a "currency manipulator". Several Bills have been introduced to discuss this issue. From a legal perspective, two entities could tackle this issue. They are the World Trade Organization (WTO) and the International Monetary Fund (IMF). However, IMF lack legitimacy and leverage and WTO has no jurisdiction over the exchange rate. So, none of these entities could handle the currency issue. Therefore, this paper analyzes some possible solutions such as Omnibus Act, tariffs, import quotas and forming new legislation. Where, it concludes that the best solution could be via forming a new international agency.